Antimalarial activity from endophytic streptomyces spp. - Baba, Mohd Shukri; Mohamad Zin, Noraziah; Latip, Jalifah (Penerbit UKM, 2021)
Alhamdulillah for the guidance from Allah s.w.t, we have succeeded publishing this scientific book entitled Antimalarial Activity from Endophytic Streptomyces spp. This book was successfully published in a timely manner along with original details from the current research by the research group of Novel Antibiotics, UKM. With a critical writing style and comprehensive scientific facts, this book is able to attract readers from all backgrounds such as researchers, academicians, students and medical practitioners. The exploration of knowledge related to the study of antimalarial drugs produced from the source of endophytic bacteria that live in certain plants and crops is very beneficial to the society and country. Therefore through this book, readers will be exposed to the importance of exploring endophytic bacteria, especially those living in trees or medicinal plants in Malaysia in an effort to find a cure for malaria that plagues this country and the world as a whole. Consisting nine chapters, this book will be consequently explained several aspects such as the both local and global distribution and situation of malaria, describing endophyte Streptomycete bacteria and their potential as a source of drugs and how the crude extracts of some Streptomyces strains can be successfully produced. Besides, in-vivo antimalarial activity of the crude extracts from these strains and antimalarial activity of the crude extracts produced by Streptomyces SUK10, as well as how the identification of Streptomyces SUK10 strain was determined were also explained. Other than that, the identification of bioactive compound namely Gancidin W which was derived from Streptomyces SUK10 that responsible for antimalarial activity, as well as in-vivo antimalarial activity and determination of toxicity effects by Gancidin W towards the mice in this study was thoroughly elaborated in this book. We deeply hope that all the knowledge described in this book can open the minds of all readers that endophyte Streptomycete bacteria that inhabited in our nature have a huge potential as a source of antimalarial drugs that need to be explored as best as possible. On this occasion, we would also like to thanks and appreciate of individuals and groups who directly or indirectly support the production of this book. The publication of this book was made possible with the financial assistant from the grant DBP-2021-158